The Impact of Using Green Hydrogen as an Alternative to Fossil Fuels in Industrial Processes to Mitigate Financial Risks: An Applied Study on the Fertilizer Sector in the Arab Republic of Egypt - Abdel Hadi, Mohamed Gamal Mohamed; Abu Bakr, Walid Zakaria Abdel Nabi (The Arab Journal of Administration, 2025)
Purpose: This study aims to assess the potential impact of green hydrogen as an alternative to fossil fuels in industrial processes, specifically focusing on its role in mitigating financial risks for fertilizer plants in Egypt. The research explores how the adoption of green hydrogen can contribute to reducing operational costs, enhancing environmental compliance, and mitigating exposure to energy price volatility, thereby promoting the long-term economic and environmental sustainability of these plants. Design, Methodology, Approach: A statistically valid questionnaire was designed and distributed to the administrative staff of fertilizer plants in Egypt. Of the 384 questionnaires distributed, 380 valid responses were collected for analysis. The questionnaire focused on measuring the perceived impact of green hydrogen on factors such as cost reduction, environmental compliance, and operational efficiency. Findings: The findings of this study indicate that the adoption of green hydrogen can significantly reduce operational costs, improve environmental compliance, and mitigate the risks associated with energy price fluctuations. The research underscores the importance of investing in necessary infrastructure and providing adequate administrative support to facilitate a smooth transition to green hydrogen in the industrial sector.